2019
DOI: 10.1002/cne.24819
|View full text |Cite
|
Sign up to set email alerts
|

Exosome/microvesicle content is altered in leucine‐rich repeat kinase 2 mutant induced pluripotent stem cell‐derived neural cells

Abstract: Extracellular vesicles, including exosomes/microvesicles (EMVs), have been described as sensitive biomarkers that represent disease states and response to therapies. In light of recent reports of disease‐mirroring EMV molecular signatures, the present study profiled two EMVs from different Parkinson's disease (PD) tissue sources: (a) neural progenitor cells derived from an endogenous adult stem/progenitor cell, called adult human neural progenitor (AHNP) cells, that we found to be pathological when isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Candelario et al reported that two kinds of exosomes were found from different Parkinson's disease (PD) tissue sources [68]. One exosome was isolated from human neural progenitor (AHNP) cells from the substantia nigra of postmortem PD patients and the other was isolated from the leucine-rich repeat kinase 2 (LRRK2) gene identified in patient iPSCs.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Candelario et al reported that two kinds of exosomes were found from different Parkinson's disease (PD) tissue sources [68]. One exosome was isolated from human neural progenitor (AHNP) cells from the substantia nigra of postmortem PD patients and the other was isolated from the leucine-rich repeat kinase 2 (LRRK2) gene identified in patient iPSCs.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Additionally, in a recent study, Candelario and colleagues characterized EVs produced by: (i) DAergic neurons derived from induced pluripotent stem cells (iPSC) carrying the LRRK2 G2019S mutation; (ii) DAergic neurons derived from iPSC of healthy sibling control; and (iii) LRRK2 G2019S edited to correct the mutation [ 138 ]. They found that EVs from all cell types were different in size and abundance.…”
Section: Other Ev-carried Pd Protein Biomarkersmentioning
confidence: 99%
“…Interestingly, the G/S correction induced the secretion of EVs whose cargo pattern was similar to control ones. Therefore the authors suggested to further analyze the content of EVs to identify potential novel biomarkers for PD [ 138 ].…”
Section: Other Ev-carried Pd Protein Biomarkersmentioning
confidence: 99%
“…LRRK2 could hold the key to unlocking answers as to why different neuropathological changes can arise from underlying genetic changes in this gene. Currently, the pathways and potential disease modifier genes that explain this striking pleomorphic presentation of LRRK2 parkinsonism and variable clinical penetrance/AAO are unknown, although many cellular phenotypes and molecular pathways, including endolysosomal stress [60][61][62], neuroinflammation [63][64][65], mitochondrial dysfunction and damage [66,67], and alterations of exosomes [68,69] have been described due to altered LRRK2 signaling. Mendelian PD genes, GWAS risk factors, and polygenic risk scores have been nominated as influencing factors for LRRK2, but studies that validate these putative modifiers are lacking.…”
Section: Lrrk2 Domain Structure and The Impact Of Inherited Mutationsmentioning
confidence: 99%